Restorative Justice Conferencing: Not a Panacea for the Overrepresentation of Australia's Indigenous Youth in the Criminal Justice System - Little, Simon (International journal of offender therapy and comparative criminology, 2018)
Restorative justice conferencing is a police diversionary strategy used extensively in Australian jurisdictions to channel young offenders away from formal court processing. Advocates view conferencing as culturally appropriate and a means to reduce the overrepresentation of Indigenous young people because it is rooted in Indigenous justice traditions. However, whether conferencing is effective at reducing recidivism by Indigenous young people compared with non-Indigenous young people remains unknown. We examine this using a longitudinal cohort of youth offenders from Australia. Propensity score matching was used to match Indigenous and non-Indigenous young people at their first conference and examined reoffending outcomes to explore its efficacy at reducing recidivism (n = 394). Results indicate that, despite statistically controlling for factors related to reoffending, recidivism levels postconference were significantly higher for Indigenous young people. These results suggest that conferencing is unlikely to address the problem of Indigenous overrepresentation within Australia's youth justice system.